QUANTITATIVE ANALYSIS -TECTONIC GEOMORFOLOGY INDICATORS OF THE FAULTS AT THE REGION OF STRATONI- VARVARA GOMATI-M. PANAGIA IN THE EASTERN CHALKIDIKI - ΜΙΧΑΗΛΙΔΟΥ, Α.; ΧΑΤΖΗΠΕΤΡΟΣ, Α.; ΠΑΥΛΙΔΗΣ, Σ. (Bulletin of the Geological Society of Greece, 2005)
The study area is located at the NE part of Chalkidiki peninsula. Geologicaly it belongs at Servomacedonian mass. The faults of Stratoni - Barbara and Gomati- M. Panagia have an important role at the surface morphology of the area. These are typically active faults and they are the most important neotectonic structures at Eastern Chaikidiki. For the study of surface morphology a quantitative morphotectonic analysis has been done with the contribution of Geographical Information Systems GIS. The morphological indicators we have studied are: hypsometric curve and hypsometric integral, drainage basin asymmetry, mountain - front sinuosity, stream length - gradient index, transverse topographic symmetry, radio of valley - floor width to valley height and fault scarp morphology. This morphotectonic analysis has confirmed the field observations. Major role in this research had the use of satellite pictures and 3D models (Digital Elevation Model - D.E.M.).